CASE STUDY OF MARINE SAFETY IN TRANSPORTING DANGEROUS GOODS - Rudianto; Arianto, Pratama Yuli; Rulianto, Jangka; Wahyudinata, Nauval Maulana Yusuf (IJMEA Journal Kedokteran Gigi, 2025)
This case study explores marine safety in transporting dangerous goods, focusing on the impact of risk management practices. Transporting hazardous cargo poses unique challenges, necessitating stringent safety measures to prevent accidents and safeguard the environment. Through a thorough analysis of maritime regulations, safety protocols, and real-world incidents, the study assesses the efficacy of safety measures and identifies areas for enhancement. The findings underscore the significance of rigorous safety protocols, crew training, and advanced technology, including real-time cargo monitoring systems and emergency response plans. Furthermore, the study highlights the importance of proactive risk assessment and continuous safety improvements. Human factors are also addressed, emphasizing the pivotal role of a well-trained and alert crew in ensuring vessel safety. In summary, this research contributes to ongoing initiatives aimed at enhancing vessel safety in the transportation of dangerous goods. It emphasizes the crucial elements of regulatory compliance, risk management, and proactive safety measures within the maritime industry.